A biomechanical comparison of two relay starts in swimming - Gambrel, D. W.; Blanke, D.; Thigpen, K.; Mellion, M. B. (Journal of Swimming Research, 1991)
The mechanical characteristics of the step and conventional starts in relay change-overs were identified. Trained male college swimmers (N = 7) served as subjects. No statistically significant differences between any parameters were found. That could be an artifact of the lack of statistical power that occurs when low subject numbers are used in a study. The conclusions of the investigation mean that the conventional and step starts are equally effective in competitive relay changes. The absolute means for the two starts, when compared, indicated the following features. 1.Time on the block was longer for the step start (.16 s) than the conventional start (.13 s). 2.Time to 10 m was faster for the step start (2.96 s) than the conventional start (3.03 s). 3.The swimmers' velocity was faster at entry (4.38 m/s) in the step start than in the conventional start (4.30 m/s). 4.The height of the center of mass at take off was higher for the step start (1.40 m) than the conventional start (1.39 m). Implication: Because of the low number of study subjects, and the majority of statistics slightly favoring the step start, this reviewer recommends adopting the step start over the conventional start if one is forced to make a selection. The preferable status is to allow experienced athletes to use the start with which they are most familiar. It should also be noted that a relay start is different to a racing start. The anticipation factor allows the athlete to move to maximize individual capacities.